2017
DOI: 10.1177/1010428317692235
|View full text |Cite
|
Sign up to set email alerts
|

Metformin augments doxorubicin cytotoxicity in mammary carcinoma through activation of adenosine monophosphate protein kinase pathway

Abstract: Since the incidence of breast cancer increases dramatically all over the world, the search for effective treatment is an urgent need. Metformin has demonstrated anti-tumorigenic effect both in vivo and in vitro in different cancer types. This work was designed to examine on molecular level the mode of action of metformin in mice bearing solid Ehrlich carcinoma and to evaluate the use of metformin in conjunction with doxorubicin as a combined therapy against solid Ehrlich carcinoma. Ehrlich ascites carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Furthermore, metformin combined with current chemotherapies in murine xenograft models of ovarian cancer (17,18) and other cancers (lung, bladder, colon, breast, etc.) has been confirmed to synergistically repress tumor growth (19)(20)(21)(22). Initial explanations attributed its effect to directly decreasing energy consumption, fatty acid, and protein synthesis via the mediation of AMPK/mTOR signaling and indirect restraint of the PI3K/AKT cascade (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, metformin combined with current chemotherapies in murine xenograft models of ovarian cancer (17,18) and other cancers (lung, bladder, colon, breast, etc.) has been confirmed to synergistically repress tumor growth (19)(20)(21)(22). Initial explanations attributed its effect to directly decreasing energy consumption, fatty acid, and protein synthesis via the mediation of AMPK/mTOR signaling and indirect restraint of the PI3K/AKT cascade (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…These results were in accordance with Ghoshal et al [18] who found that female SD rats that treated orally with PhIP showed different phenotypes of mammary tumors including intraductal carcinoma (papillary, cribriform, and comedo type) and tubular adenocarcinoma. A study by El‐Ashmawy et al [35] demonstrated that Met alone or in combination with Dox showed enhanced apoptosis and absence of necrosis in tumor tissue of co‐treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in accordance with Ghoshal et al 21 who found that female SD rats that treated orally with PhIP showed different phenotypes of mammary tumors including intraductal carcinoma (papillary, cribriform, and comedotype) and tubular adenocarcinoma. In addition, a study by El-Ashmawy et al 28 demonstrated that metformin alone or in combination with doxorubicin reduced the tumor volume of solid Ehrlich carcinoma mice, and this effect was mediated through AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%